Бабочка на стекле: роман / Джузи Эркетт - Джузи Эркетт (Панорама романов о любви, 1996)
Экземпляры: Ф. 10 (20200625) / Инвентарный номер: 47880 / Цена: 14.00 / Сис.шифр: 84(7Coe) / Авт.знак: Э 78 / ГРНТИ: 17.82 / ББК: 84(7Coe)